Overweight older adults, particularly after an injury, are at high risk for accelerated knee osteoarthritis: data from the Osteoarthritis Initiative. Issue 4 (April 2016) - Driban, Jeffrey; Eaton, Charles; Lo, Grace; Price, Lori; Lu, Bing; Barbe, Mary; McAlindon, Timothy
Abstract We explored whether age and body mass index (BMI) can help identify a subset of individuals who are at high risk for accelerated knee osteoarthritis (AKOA) compared with common knee osteoarthritis (KOA). In the Osteoarthritis Initiative, a multicenter observational cohort study of KOA (n  = 4796), we studied participants without KOA at baseline (Kellgren-Lawrence (KL) <2). Participants could have one of three outcomes: (1) AKOA, ≥1 knee progressed to end-stage KOA within 48 months; (2) common KOA, ≥1 knee increased in radiographic scoring within 48 months (excluding those with AKOA); and (3) no KOA, no change in KL grade in either knee. After verifying an interaction between age, BMI, and recent knee injury, we determined if we could identify a specific subset of individuals at high risk for AKOA instead of KOA. First, we reviewed three-dimensional graphs with age, BMI, and probability of AKOA versus KOA on the axes. We then conducted a logistic regression with AKOA as the outcome and age-BMI groups as the predictor. In our main analyses, we found that older individuals with a BMI <35 kg/m2 were more likely to develop AKOA than common KOA (n  = 64; mean [SD] BMI = 27.3 [3.1] kg/m2 ; odds ratio = 3.47, 95 % confidence interval = 1.70 to 7.10), especially if they had a recent knee injury. While older age and greater BMI are independently associated with AKOA, we found that older individuals who had a higher BMI, particularly if they have an injury, were more likely to develop AKOA than common KOA.